Effects of ultrasound on bubble dynamic behavior of flow boiling in microchannel - Yong Guo; Qingqing Zhu; Shiliang Song; Yan Li; Zongbo Zhang; Liang Gong (Ultrasonics Sonochemistry, 2024)
Bubble dynamics is paramount in comprehending the heat transfer mechanisms of flow boiling in the microchannel within ultrasonic field, which is regarded as a promising method to confront challenges of thermal management posed by microelectronic devices. Nevertheless, the impact of ultrasound on bubble behaviors and its underlying mechanisms remain largely unexplored. This study first delves into the effect of ultrasonic parameters on bubble dynamic behaviors and associated mechanisms, subsequently further analyzing the forces acting on bubbles through the constructed force model. The findings suggest that although growth force serves as the significant resistance, the primary Bjerknes force dominates the rapid detachment of bubbles. The secondary Bjerknes force results in the bubble only sliding along the bottom wall rather than lifting off. Furthermore, the elevated ultrasonic pressure amplitude resulting from augmenting ultrasonic power induces a substantial increase in the critical detachment diameter and growth rate by 55.49 % and 59.42 %, respectively. The enhanced primary Bjerknes force, attributed to the rise in ultrasonic frequency, leads to a 71.42 % increase in sliding velocity and a 46.45 % reduction in growth time. The positive impacts arising from ultrasonic power and frequency are anticipated to notably enhance the thermal performance of microchannels. Besides, surface tension acts as the resistance and diminishes slightly with an augmentation of the boiling number, resulting in a moderate variation in sliding velocity and growth time.